Resenha de Bellucci, Francesco. Charles S. Peirce. Selected Writings on Semiotics, 1894–1912, Berlin, Boston: De Gruyter Mouton, 2020. https://doi.org/10.1515/9783110607390 - Rodrigues, Cassiano Terra (Cognitio: Revista de Filosofia, 2022)
Resenha de Bellucci, Francesco. Charles S. Peirce. Selected Writings on Semiotics, 1894–1912, Berlin, Boston: De Gruyter Mouton, 2020. https://doi.org/10.1515/9783110607390